Using gel pillows in preterm infants is related to decreased cranial deformity - Nayadet Lucero; Alicia Nuñez; Bernardita Severín de la M.; Raúl Escobar (Revista Chilena de Terapia Ocupacional, 2016)
Introduction: The positional scaphocephaly is the preterm infants’ typical cranial deformity. And probably is due to improper motor control, which determines minor change in position and longer asymmetric pressure on the skull. Decreasing the pressure of asymmetric support points on the skull, might decrease scaphocephaly. Gel’s surface may decrease localized pressure in the skull thus decreasing the stiffness of the contact surface. There are scarce reports about this issue and all are inconclusive.Objective: To show the relationship between the use of gel pillows and reduction of scaphocephaly in preterm infants.Method: Longitudinal study of preterm infants hospitalized in neonatology service of a tertiary hospital. They used gel pillows for 5 consecutive weeks, for at least 90% of the time in prone position. Cranial measurements were performed, considering the index of cranial deformity, the first measurement before to the use of pillows and then weekly until 5 weeks.Results: 17 patients completed the 5-week protocol. Average age 28.9 weeks of gestation (range 28-34), average weight 1058 g. (range 720-2000). The index of cranial deformity ranged from 70.36 (SD 4.7) at baseline to 76.95 (3.03) at the end of the study with a significant difference (p